Evaluation of Mechanical Characterization of CFRP Reinforced Stainless Steel (SS304) Wire Mesh Polymer Composite. (July 2019) - Naga Kiran, S.D.; Jayakumar, V.; Madhu, S.
Abstract: In recent days, fibre metal hybrid composites have been utilized for improve the stiffness, excellent corrosion resistance, low density and less weight. CFRP reinforced stainless steel (SS) wire mesh hybrid fibre metal laminate has been fabricated using hand layup process. Viscoelastic properties of fabricated composite samples have been studied by using Dynamic Mechanical Analysis (DMA) test. Mechanical characterization such as Dynamic Mechanical Analysis (DMA), Flexural test and tensile properties of the newly fabricated fibre metal laminated also investigated. The DMA parameters such as storage modulus (E'), loss modulus (E") and damping factor (tan δ) has been investigated. Flexural test has been performed for evaluating the bending stress. DMA results revealed that storage modulus of E' was maximum at 5 Hz. In this work tensile strength observed was 533.05 MPa at 16.19 KN. For Flexural strength obtained in the fabricated composite material was 1.03 KN.